A positive electrode material of metal oxide coated sodium iron fluorophosphate, a preparation method and application thereof
Patent Information
- Application Number
- CN202611100919.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-20
AI Technical Summary
然而,常规金属氧化物湿法包覆通常直接将金属盐前驱体、沉淀剂与正极材料混合,金属前驱体容易在溶液中发生均相沉淀,导致包覆物难以优先沉积于氟磷酸铁钠颗粒表面,进而出现包覆层分布不均、局部包覆过厚、颗粒团聚及游离氧化物杂质增多等问题
本发明通过“膦酸盐锚定预处理-铝盐封端引发-铝锆络合前驱液预吸附老化-尿素缓释沉积-补钠补氟低温热处理”的连续工艺,对氟磷酸铁钠基体表面进行受控金属氧化物包覆。与常规直接将金属盐和沉淀剂混合沉积的湿法包覆方式相比,本发明先利用1-羟基乙叉-1,1-二膦酸钠盐在氟磷酸铁钠表面形成可与铝离子相互作用的锚定界面,并通过洗涤减少游离膦酸盐对后续铝锆离子的过度络合;随后引入低量铝盐进行封端引发,使铝锆络合前驱液更容易在颗粒表面预吸附,而不是在溶液中直接形成游离沉淀;再通过尿素加热缓慢释放碱性组分,实现铝锆复合前驱层的温和沉积,从而有利于减少包覆不均、局部厚包覆、颗粒团聚和游离氧化物杂质。低温热处理阶段配合氟化钠和磷酸二氢钠补钠补氟组分,可降低湿法处理及热处理过程对氟磷酸铁钠表面钠、氟、磷环境的扰动,使形成的包含Al2O3和ZrO2的复合氧化物包覆层兼具界面保护和离子传输协调作用。
Smart Images

Figure REF-OBJ-1784786998337-000002 
Figure REF-OBJ-1784786998337-000003
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of sodium-ion battery cathode materials, specifically relating to a metal oxide-coated sodium fluorophosphate cathode material, its preparation method, and its application. Background Technology
[0002] Sodium-ion batteries have received widespread attention in recent years due to the abundance of sodium resources, low cost, and suitability for large-scale energy storage applications. The cathode material is a key factor affecting the capacity, rate performance, and cycle life of sodium-ion batteries. Sodium iron fluorophosphate, a polyanionic sodium-ion battery cathode material, has advantages such as good structural stability, high operating voltage, and abundant iron-based raw material sources. However, it still suffers from limited electronic conductivity, easy side reactions between the particle surface and the electrolyte, and increased interfacial impedance during cycling, which affect its high-rate and long-cycle applications.
[0003] Current research mainly focuses on modification through carbon coating, elemental doping, and inorganic surface coating. Carbon coating can improve electron transport, but its inhibitory effect on interfacial side reactions is limited. Elemental doping can adjust crystal structure and ion transport performance, but the doping amount and position are difficult to control, and excessive doping may introduce impurity phases. Metal oxide coating can isolate the active material from the electrolyte to a certain extent, improving interfacial stability. However, conventional wet metal oxide coating usually involves directly mixing the metal salt precursor, precipitant, and cathode material. The metal precursor is prone to homogeneous precipitation in the solution, making it difficult for the coating material to preferentially deposit on the surface of sodium fluorophosphate particles. This leads to problems such as uneven coating layer distribution, excessively thick local coatings, particle agglomeration, and increased free oxide impurities. If the coating amount is insufficient, it is difficult to form effective interfacial protection; if the coating is too thick, it may hinder sodium ion migration and reduce rate performance. In addition, the sodium, fluorine, and phosphorus environment on the surface of sodium fluorophosphate may be disturbed during wet processing and subsequent heat treatment, further affecting the interfacial stability of the material. Summary of the Invention
[0004] To address the shortcomings mentioned in the background art, the present invention aims to provide a method for preparing and applying a metal oxide-coated sodium fluorophosphate cathode material. The method involves first pretreating the sodium fluorophosphate matrix with phosphonate anchoring, followed by washing and then introducing aluminum salts for end-capping initiation. Next, an aluminum-zirconium complex precursor solution is added for pre-adsorption aging. Subsequently, an aluminum-zirconium composite precursor layer is formed through urea slow-release deposition, and finally, a low-temperature heat treatment with added sodium and fluorine yields a cathode material containing an Al₂O₃ and ZrO₂ composite oxide coating layer. This invention reduces free precipitation and localized thick coating phenomena, improving the material's interfacial stability.
[0005] The objective of this invention can be achieved through the following technical solutions: A method for preparing a cathode material of sodium fluorophosphate coated with a metal oxide, wherein the metal oxide is a composite oxide containing Al2O3 and ZrO2, and the preparation method includes the following steps performed sequentially: S1. The sodium fluorophosphate matrix was dispersed in an ethanol-water system containing citrate, sodium dihydrogen phosphate, sodium fluoride and sodium 1-hydroxyethylidene-1,1-diphosphonate for phosphonate anchoring pretreatment. After solid-liquid separation and washing with an ethanol-water mixture, the phosphonate-anchored sodium fluorophosphate was obtained. S2. The sodium fluorophosphate pretreated with phosphonate anchoring obtained in step S1 is redispersed in an ethanol-water system, and aluminum salt is added for end-capping initiation treatment to obtain sodium fluorophosphate pretreated with aluminum end-capping. S3. Add an aluminum-zirconium complex precursor solution prepared by an aluminum source, a zirconium source and a complexing agent to the aluminum-end pretreated sodium fluorophosphate dispersion system obtained in step S2, and perform pre-adsorption aging treatment before adding urea in step S4. S4. After the pre-adsorption aging treatment described in step S3 is completed, urea is added and slow-release deposition is carried out under heating conditions to obtain sodium fluorophosphate coated with an aluminum-zirconium composite precursor layer. S5. After solid-liquid separation, washing and drying, the sodium fluorophosphate coated with the aluminum-zirconium composite precursor layer obtained in step S4 is mixed with a sodium- and fluorine-supplementing component including sodium fluoride and sodium dihydrogen phosphate, and subjected to low-temperature heat treatment under an inert atmosphere to obtain the positive electrode material of sodium fluorophosphate coated with metal oxide.
[0006] In step S1, the sodium ferric fluorophosphate matrix is selected from at least one of Na2FePO4F matrix particles and carbon-coated Na2FePO4F matrix particles; the volume ratio of ethanol to water in the ethanol-water system is 30:70 to 70:30; the citrate is sodium citrate; and the sodium 1-hydroxyethylidene-1,1-diphosphonate is selected from at least one of disodium 1-hydroxyethylidene-1,1-diphosphonate and tetrasodium 1-hydroxyethylidene-1,1-diphosphonate.
[0007] In step S1, the concentration of sodium dihydrogen phosphate is 0.005–0.05 mol / L, the amount of sodium fluoride is 0.02–0.20% of the mass of sodium ferric fluorophosphate matrix, the amount of sodium 1-hydroxyethylidene-1,1-diphosphonate is 0.02–0.12% of the mass of sodium ferric fluorophosphate matrix, and the pH of the phosphonate anchoring pretreatment is 5.5–6.8.
[0008] In step S1, the washing is a single immersion using an ethanol-water mixture, and the washing time is 2 to 10 minutes.
[0009] In step S2, the aluminum salt is selected from at least one of aluminum nitrate and its hydrate, aluminum chloride and its hydrate, and aluminum isopropoxide, and the amount of the aluminum salt is 0.02 to 0.20% of the mass of the sodium fluorophosphate matrix, calculated as Al2O3.
[0010] In step S3, the aluminum source is selected from at least one of aluminum nitrate nonahydrate, aluminum chloride hexahydrate, and aluminum isopropoxide; the zirconium source is selected from at least one of zirconium oxychloride octahydrate, zirconium nitrate, and zirconium acetate; and the complexing agent is selected from at least one of citric acid, lactic acid, and malic acid.
[0011] In step S3, the aluminum source and zirconium source are added at a molar ratio of Al:Zr of 1:(0.1-0.8). The ratio of the total molar amount of aluminum and zirconium in the complexing agent to the total molar amount of aluminum and zirconium in the aluminum-zirconium complexing precursor solution in step S3 is 0.5-2.0:1. The total amount of aluminum salt in step S2, aluminum source in step S3, and zirconium source in step S3, after being converted to Al2O3 and ZrO2 respectively based on the amount of feed, is 0.3-2.0% of the mass of sodium ferric fluorophosphate matrix.
[0012] In step S4, the total molar ratio of aluminum and zirconium in the urea to that in the aluminum-zirconium complex precursor solution in step S3 is 5-30:1, the temperature of the slow-release deposition is 75-90°C, and the pH at the endpoint of the slow-release deposition is 6.5-8.0.
[0013] In step S5, the washing is performed using at least one of deionized water and an ethanol-water mixture; the sodium and fluoride supplementation components include sodium fluoride and sodium dihydrogen phosphate, wherein the amount of sodium fluoride is 0.02-0.30% of the mass of the sodium ferric fluorophosphate matrix, and the amount of sodium dihydrogen phosphate is 0.02-0.20% of the mass of the sodium ferric fluorophosphate matrix; the low-temperature heat treatment is performed at a temperature of 300-380°C for 1-4 hours, and the inert atmosphere is nitrogen or argon.
[0014] A cathode material of sodium fluorophosphate coated with a metal oxide, the cathode material comprising sodium fluorophosphate matrix particles and a composite oxide coating layer formed on at least a portion of the surface of the sodium fluorophosphate matrix particles, the composite oxide coating layer comprising Al2O3 and ZrO2.
[0015] The beneficial effects of this invention are: This invention employs a continuous process of "phosphonate anchoring pretreatment - aluminum salt end-capping initiation - aluminum-zirconium complex precursor solution pre-adsorption aging - urea slow-release deposition - sodium and fluorine supplementation low-temperature heat treatment" to achieve controlled metal oxide coating on the surface of sodium fluorophosphate substrates. Compared to conventional wet coating methods that directly mix and deposit metal salts and precipitants, this invention first utilizes sodium 1-hydroxyethylidene-1,1-diphosphonate to form an anchoring interface on the sodium fluorophosphate surface that can interact with aluminum ions, and reduces excessive complexation of subsequent aluminum-zirconium ions by free phosphonates through washing; subsequently, a low amount of aluminum salt is introduced for end-capping initiation, making it easier for the aluminum-zirconium complex precursor solution to pre-adsorb on the particle surface, rather than directly forming free precipitates in the solution; then, the alkaline components are slowly released by heating urea to achieve gentle deposition of the aluminum-zirconium composite precursor layer, thereby helping to reduce uneven coating, localized thick coating, particle agglomeration, and free oxide impurities. The use of sodium fluoride and sodium dihydrogen phosphate as sodium and fluorine supplementation components during the low-temperature heat treatment stage can reduce the disturbance of the sodium, fluorine, and phosphorus environment on the surface of sodium ferric fluorophosphate during wet treatment and heat treatment processes, so that the resulting composite oxide coating layer containing Al2O3 and ZrO2 has both interface protection and ion transport coordination functions. Attached Figure Description
[0016] The invention will now be further described with reference to the accompanying drawings.
[0017] Figure 1 This is a flowchart of the preparation method of the present invention. Detailed Implementation
[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] In the following examples and comparative examples, the carbon-coated Na2FePO4F matrix particles used were from the same batch of materials; the sodium citrate, sodium dihydrogen phosphate, sodium fluoride, tetrasodium 1-hydroxyethylidene-1,1-diphosphonate, aluminum nitrate nonahydrate, zirconium oxychloride octahydrate, citric acid, urea, ethanol and deionized water used were all commercially available reagents.
[0020] All percentages mentioned in the examples are mass percentages relative to the mass of the sodium ferric fluorophosphate matrix; the total amount of aluminum source and zirconium source converted to Al2O3 and ZrO2 according to the feeding amount respectively refers to the amount of oxides converted according to the theoretical feeding amount of aluminum source and zirconium source.
[0021] When the zirconium source is a chlorine-containing metal source such as zirconium oxychloride octahydrate, the soluble chloride and nitrate residues are reduced by multiple washings with deionized water and alcohol water after deposition.
[0022] Example 1: This example provides a method for preparing a metal oxide-coated sodium fluorophosphate cathode material. Unless otherwise specified, the volume ratio of ethanol to water in the ethanol-water mixture described in this example is 30:70.
[0023] S1. Weigh 100g of carbon-coated Na2FePO4F matrix particles and add them to 1000mL of ethanol-water mixture. Stir and disperse for 30min to obtain a sodium fluorophosphate matrix dispersion. Add sodium citrate to the sodium fluorophosphate matrix dispersion to make the sodium citrate concentration 0.01mol / L, add sodium dihydrogen phosphate to make the sodium dihydrogen phosphate concentration 0.005mol / L, then add 0.02g of sodium fluoride and 0.02g of tetrasodium 1-hydroxyethylidene-1,1-diphosphonate. Adjust the pH of the system to 5.5 with 0.1mol / L sodium hydroxide solution and stir at 40℃ for 20min. After treatment, perform solid-liquid separation and wash the obtained solid once with 200mL of ethanol-water mixture for 2min to obtain phosphonate-anchored pretreated sodium fluorophosphate.
[0024] S2. The sodium fluorophosphate pretreated with phosphonate anchoring obtained in step S1 is redispersed in 1000 mL of ethanol-water mixture, 0.147 g of aluminum nitrate nonahydrate is added, and the mixture is stirred at 40 °C for 10 min to obtain a sodium fluorophosphate dispersion system with aluminum end-capping pretreatment.
[0025] S3. Weigh 1.659 g of aluminum nitrate nonahydrate, 0.143 g of zirconium oxychloride octahydrate, and 0.467 g of citric acid, add them to 100 mL of ethanol-water mixture and stir to dissolve, preparing an aluminum-zirconium complex precursor solution; wherein the molar ratio of aluminum to zirconium (Al:Zr) is 1:0.1, and the molar ratio of citric acid to the total molar amounts of aluminum and zirconium is 0.5:1. Without adding urea, add the aluminum-zirconium complex precursor solution to the aluminum-terminated sodium fluorophosphate dispersion system obtained in step S2, and stir for pre-adsorption and aging at 50 °C for 30 min.
[0026] S4. After the pre-adsorption aging treatment described in step S3 is completed, 1.46 g of urea is added to the system. The molar ratio of urea to the total amount of aluminum and zirconium is 5:1. Then, the temperature is increased to 75 °C at 2 °C / min for slow-release deposition for about 1 hour. During the slow-release deposition process, a temperature-compensated pH electrode is used to monitor the pH of the system in situ. The pH reaches 6.5 at the end of the deposition process, resulting in sodium fluorophosphate coated with an aluminum-zirconium composite precursor layer.
[0027] S5. The sodium fluorophosphate coated with the aluminum-zirconium composite precursor layer obtained in step S4 is subjected to solid-liquid separation. The obtained solid is washed three times with deionized water, each time using 300 mL of deionized water, and then washed once with 200 mL of ethanol-water mixture. After washing, it is dried at 80 °C for 12 h. The dried solid is mixed with 0.02 g of sodium fluoride and 0.02 g of sodium dihydrogen phosphate by dry mixing for 10 min. Then, under a nitrogen atmosphere, the temperature is increased to 300 °C at 3 °C / min and held for 1 h to obtain the metal oxide coated sodium fluorophosphate cathode material.
[0028] Example 2: This example provides a method for preparing a metal oxide-coated sodium fluorophosphate cathode material. Unless otherwise specified, the volume ratio of ethanol to water in the ethanol-water mixture described in this example is 70:30.
[0029] S1. Weigh 100g of carbon-coated Na2FePO4F matrix particles and add them to 1000mL of ethanol-water mixture. Stir and disperse for 30min to obtain a sodium fluorophosphate matrix dispersion. Add sodium citrate to the sodium fluorophosphate matrix dispersion to make the sodium citrate concentration 0.08mol / L, add sodium dihydrogen phosphate to make the sodium dihydrogen phosphate concentration 0.05mol / L, then add 0.20g of sodium fluoride and 0.12g of tetrasodium 1-hydroxyethylidene-1,1-diphosphonate. Adjust the pH of the system to 6.8 with 0.1mol / L sodium hydroxide solution and stir at 60℃ for 90min. After treatment, perform solid-liquid separation and wash the obtained solid once with 200mL of ethanol-water mixture for 10min to obtain phosphonate-anchored pretreated sodium fluorophosphate.
[0030] S2. The sodium fluorophosphate pretreated with phosphonate anchoring obtained in step S1 is redispersed in 1000 mL of ethanol-water mixture, 1.472 g of aluminum nitrate nonahydrate is added, and the mixture is stirred at 60 °C for 60 min to obtain an aluminum-terminated sodium fluorophosphate dispersion system.
[0031] S3. Weigh 4.515g of aluminum nitrate nonahydrate, 3.103g of zirconium oxychloride octahydrate, and 8.325g of citric acid, add them to 200mL of ethanol-water mixture and stir to dissolve, preparing an aluminum-zirconium complex precursor solution; wherein the molar ratio of aluminum to zirconium (Al:Zr) is 1:0.8, and the molar ratio of citric acid to the total molar amounts of aluminum and zirconium is 2.0:1. Without adding urea, add the aluminum-zirconium complex precursor solution to the aluminum-terminated sodium fluorophosphate dispersion system obtained in step S2, and stir for pre-adsorption aging at 70℃ for 120min.
[0032] S4. After the pre-adsorption aging treatment described in step S3 is completed, 39.03g of urea is added to the system. The molar ratio of urea to aluminum and zirconium is 30:1. Then, the temperature is increased to 90℃ at 2℃ / min for slow-release deposition for about 4 hours. During the slow-release deposition process, a temperature-compensated pH electrode is used to monitor the pH of the system in situ. The pH reaches 8.0 at the deposition endpoint, resulting in sodium fluorophosphate coated with an aluminum-zirconium composite precursor layer.
[0033] S5. The sodium fluorophosphate coated with the aluminum-zirconium composite precursor layer obtained in step S4 is subjected to solid-liquid separation. The obtained solid is washed four times with deionized water, each time using 300 mL of deionized water, and then washed once with 200 mL of ethanol-water mixture. After washing, it is dried at 80 °C for 12 h. The dried solid is mixed with 0.30 g of sodium fluoride and 0.20 g of sodium dihydrogen phosphate by dry mixing for 10 min. Then, under an argon atmosphere, the temperature is increased to 380 °C at 3 °C / min and held for 4 h to obtain the metal oxide coated sodium fluorophosphate cathode material.
[0034] Example 3: This example provides a method for preparing a metal oxide-coated sodium fluorophosphate cathode material. Unless otherwise specified, the volume ratio of ethanol to water in the ethanol-water mixture described in this example is 50:50.
[0035] S1. Weigh 100g of carbon-coated Na2FePO4F matrix particles and add them to 1000mL of ethanol-water mixture. Stir and disperse for 30min to obtain a sodium fluorophosphate matrix dispersion. Add sodium citrate to the sodium fluorophosphate matrix dispersion to make the sodium citrate concentration 0.03mol / L, add sodium dihydrogen phosphate to make the sodium dihydrogen phosphate concentration 0.02mol / L, then add 0.08g of sodium fluoride and 0.06g of tetrasodium 1-hydroxyethylidene-1,1-diphosphonate. Adjust the pH of the system to 6.2 with 0.1mol / L sodium hydroxide solution and stir at 50℃ for 60min. After treatment, perform solid-liquid separation and wash the obtained solid once with 200mL of ethanol-water mixture for 5min to obtain phosphonate-anchored pretreated sodium fluorophosphate.
[0036] S2. The sodium fluorophosphate pretreated with phosphonate anchoring obtained in step S1 is redispersed in 1000 mL of ethanol-water mixture, 0.589 g of aluminum nitrate nonahydrate is added, and the mixture is stirred at 50 °C for 30 min to obtain an aluminum-terminated sodium fluorophosphate dispersion system.
[0037] S3. Weigh 2.694 g of aluminum nitrate nonahydrate, 0.925 g of zirconium oxychloride octahydrate, and 1.932 g of citric acid, add them to 100 mL of ethanol-water mixture and stir to dissolve, preparing an aluminum-zirconium complex precursor solution; wherein the molar ratio of aluminum to zirconium (Al:Zr) is 1:0.4, and the molar ratio of citric acid to the total molar amounts of aluminum and zirconium is 1.0:1. Without adding urea, add the aluminum-zirconium complex precursor solution to the aluminum-terminated sodium fluorophosphate dispersion system obtained in step S2, and stir for pre-adsorption and aging at 60 °C for 60 min.
[0038] S4. After the pre-adsorption aging treatment described in step S3 is completed, 9.06 g of urea is added to the system. The molar ratio of urea to the total amount of aluminum and zirconium is 15:1. Then, the temperature is increased to 85°C at 2°C / min for slow-release deposition for about 2 hours. During the slow-release deposition process, a temperature-compensated pH electrode is used to monitor the pH of the system in situ. The pH reaches 7.2 at the end of the deposition process, resulting in sodium fluorophosphate coated with an aluminum-zirconium composite precursor layer.
[0039] S5. The sodium fluorophosphate coated with the aluminum-zirconium composite precursor layer obtained in step S4 is subjected to solid-liquid separation. The obtained solid is washed three times with deionized water, each time using 300 mL of deionized water, and then washed once with 200 mL of ethanol-water mixture. After washing, it is dried at 80 °C for 12 h. The dried solid is mixed with 0.10 g of sodium fluoride and 0.08 g of sodium dihydrogen phosphate by dry mixing for 10 min. Then, under a nitrogen atmosphere, the temperature is increased to 340 °C at 3 °C / min and held for 2 h to obtain the metal oxide coated sodium fluorophosphate cathode material.
[0040] Comparative Example 1: This comparative example serves as a basic blank control without undergoing the metal oxide coating modification process of this invention.
[0041] 100g of carbon-coated Na2FePO4F matrix particles were weighed and used directly as the sodium fluorophosphate cathode material of Comparative Example 1 without phosphonate anchoring pretreatment, aluminum salt end-capping initiation treatment, aluminum zirconium complex precursor liquid pre-adsorption aging, urea slow-release deposition and sodium and fluorine supplementation low-temperature heat treatment.
[0042] The difference between this comparative example and Example 3 is that the phosphonate anchoring, aluminum salt end-capping, aluminum zirconium pre-adsorption deposition, and sodium and fluorine supplementation low-temperature heat treatment processes of the present invention were not performed. This was used to investigate the effect of the overall coating modification process of the present invention on the performance of sodium fluorophosphate cathode material.
[0043] Comparative Example 2: This comparative example provides a method for preparing a metal oxide-coated sodium fluorophosphate cathode material. The difference between this comparative example and Example 3 is that 1-hydroxyethylidene-1,1-diphosphonate tetrasodium is not added in step S1, while the remaining raw material amounts, preparation steps and process conditions are the same as in Example 3.
[0044] Specifically, in step S1, 100g of carbon-coated Na2FePO4F matrix particles are weighed and added to 1000mL of ethanol-water mixture. The mixture is stirred and dispersed for 30min to obtain a sodium fluorophosphate matrix dispersion. Sodium citrate is added to the sodium fluorophosphate matrix dispersion to achieve a sodium citrate concentration of 0.03mol / L, sodium dihydrogen phosphate is added to achieve a sodium dihydrogen phosphate concentration of 0.02mol / L, and then 0.08g of sodium fluoride is added. Tetrasodium 1-hydroxyethylidene-1,1-diphosphonate is not added. The pH of the system is adjusted to 6.2 using 0.1mol / L sodium hydroxide solution, and the mixture is stirred at 50℃ for 60min. After treatment, solid-liquid separation is performed, and the obtained solid is washed once with 200mL of ethanol-water mixture for 5min to obtain pretreated sodium fluorophosphate.
[0045] Subsequently, following steps S2 to S5 of Example 3, aluminum salt treatment, aluminum-zirconium complex precursor liquid pre-adsorption aging, urea deposition, washing and drying, and low-temperature heat treatment were performed to obtain the cathode material of Comparative Example 2.
[0046] Comparative Example 3: This comparative example provides a method for preparing a metal oxide-coated sodium fluorophosphate cathode material without aluminum salt end-capping initiation treatment. The difference between this comparative example and Example 3 is that the aluminum salt end-capping initiation treatment in step S2 of Example 3 is not performed, and the sodium fluorophosphate obtained from step S1 with phosphonate anchoring pretreatment is directly subjected to pre-adsorption aging of aluminum zirconium complex precursor solution.
[0047] Specifically, after preparing sodium fluorophosphate with phosphonate anchoring pretreatment according to step S1 of Example 3, it is redispersed in 1000 mL of ethanol-water mixture, wherein the volume ratio of ethanol to water in the ethanol-water mixture is 50:50.
[0048] Weigh 2.993 g of aluminum nitrate nonahydrate, 1.029 g of zirconium oxychloride octahydrate, and 2.146 g of citric acid, and add them to 100 mL of ethanol-water mixture and stir to dissolve, preparing an aluminum-zirconium complex precursor solution; wherein the molar ratio of aluminum to zirconium (Al:Zr) is 1:0.4, and the molar ratio of citric acid to the total molar amounts of aluminum and zirconium is 1.0:1. Without the addition of urea, the aluminum-zirconium complex precursor solution is added to the above dispersion system, and the mixture is stirred and pre-adsorbed for 60 min at 60 °C.
[0049] After the pre-adsorption aging treatment, 10.07 g of urea was added to the system, with a molar ratio of urea to aluminum and zirconium of 15:1. The system was then heated to 85 °C at a rate of 2 °C / min for slow-release deposition for approximately 2 hours. During the slow-release deposition process, a temperature-resistant pH electrode was used to monitor the pH of the system in situ. The pH reached 7.2 at the final deposition point, yielding sodium fluorophosphate treated with the aluminum-zirconium composite precursor.
[0050] Subsequently, following step S5 of Example 3, solid-liquid separation, washing, drying, sodium and fluorine supplementation mixing, and low-temperature heat treatment were performed to obtain the cathode material of Comparative Example 3.
[0051] Comparative Example 4: This comparative example provides a method for preparing a metal oxide-coated sodium fluorophosphate cathode material by simultaneously adding aluminum zirconium complex precursor solution and urea. The difference between this comparative example and Example 3 is that the pre-adsorption aging treatment of the aluminum zirconium complex precursor solution without the addition of urea is not performed as in Example 3. Instead, the aluminum zirconium complex precursor solution and urea are simultaneously added to the aluminum-terminated sodium fluorophosphate dispersion system.
[0052] Specifically, an aluminum-capped pretreated sodium fluorophosphate dispersion system was prepared according to steps S1 and S2 of Example 3.
[0053] Weigh 2.694 g of aluminum nitrate nonahydrate, 0.925 g of zirconium oxychloride octahydrate, and 1.932 g of citric acid, add them to 100 mL of ethanol-water mixture and stir to dissolve. The volume ratio of ethanol to water in the ethanol-water mixture is 50:50. Prepare an aluminum-zirconium complex precursor solution. The molar ratio of aluminum to zirconium (Al:Zr) is 1:0.4, and the molar ratio of citric acid to the total molar amount of aluminum and zirconium is 1.0:1.
[0054] The aluminum-zirconium complex precursor solution and 9.06 g of urea were simultaneously added to the aluminum-terminated pretreated sodium fluorophosphate dispersion system, with the molar ratio of urea to the total molar amounts of aluminum and zirconium being 15:1. Subsequently, the temperature was increased to 85 °C at 2 °C / min for deposition treatment for approximately 2 hours. During the deposition process, a temperature-resistant pH electrode was used to monitor the pH of the system in situ. The pH reached 7.2 at the final deposition point, yielding sodium fluorophosphate treated with the aluminum-zirconium complex precursor.
[0055] Subsequently, following step S5 of Example 3, solid-liquid separation, washing, drying, sodium and fluorine supplementation mixing, and low-temperature heat treatment were performed to obtain the cathode material of Comparative Example 4.
[0056] Performance testing To verify the electrochemical performance of the metal oxide-coated sodium fluorophosphate cathode material obtained in this invention, the cathode materials obtained in Examples 1-3 and Comparative Examples 1-4 were prepared into coin cells, and the initial discharge specific capacity, rate performance, room temperature cycling performance, high temperature cycling performance, and post-cycle impedance were tested.
[0057] 1. Battery manufacturing The positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-4 were used as active materials. The active materials, conductive carbon black, and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. N-methylpyrrolidone was added and the mixture was ground into a slurry. The slurry was then uniformly coated onto an aluminum foil current collector, vacuum dried at 80°C for 12 hours, rolled, and cut into positive electrode sheets. The active material loading in the positive electrode sheets was 2.0 ± 0.2 mg / cm³. 2 The electrical performance testing of sodium-ion batteries can refer to the evaluation approach of GB / T 44265-2024 "Technical Specification for Sodium-ion Batteries in Power Storage Stations".
[0058] A CR2032 coin cell was assembled in an argon-filled glove box using a sodium metal sheet as both the counter and reference electrodes, a glass fiber membrane as the separator, and 1.0 mol / L NaClO4 / EC+DMC+FEC as the electrolyte. The volume ratio of EC to DMC was 1:1, and the volume fraction of FEC was 5%. After assembly, the cells were allowed to stand for 12 hours before electrochemical testing. Based on the theoretical specific capacity of the carbon-coated sodium fluorophosphate cathode material, the current density corresponding to a 1C rate was defined as 124 mA / g.
[0059] 2. First discharge specific capacity test The assembled button cell was subjected to constant current charge-discharge test at 25±2℃ with a 0.2C rate in the voltage range of 2.0 to 4.2V, and the first discharge specific capacity was recorded.
[0060] 3. Ratio Performance Test The coin cell was subjected to constant current charge-discharge tests at 0.2C, 0.5C, 1C, 2C and 5C rates at 25±2℃, with 5 cycles at each rate. The discharge specific capacity at the 5th cycle at the 5C rate was recorded to evaluate the rate performance of the material.
[0061] 4. Room temperature cycling performance test The coin cell was activated at 25±2℃ for 3 cycles at a 0.2C rate, and then cycled 200 times at a 1C rate within a voltage range of 2.0–4.2V. The capacity retention rate after the 200th cycle was recorded. The baseline capacity for capacity retention rate is the discharge specific capacity of the first cycle after activation and formal entry into the 1C long cycle, excluding the capacity of the initial 0.2C activation cycle.
[0062] Capacity retention is calculated using the following formula: Capacity retention rate = discharge specific capacity of Nth cycle / discharge specific capacity of the first cycle of the formal 1C long cycle × 100%.
[0063] 5. High-temperature cycling performance test The coin cell was placed in a constant temperature environment of 45℃ and activated at 0.2C for 3 cycles. Then, it was cycled 100 times at 1C within a voltage range of 2.0 to 4.2V. The capacity retention rate after the 100th cycle was recorded. The baseline capacity for capacity retention rate is the discharge specific capacity of the first cycle after activation under high temperature conditions and formal entry into the 1C long cycle, excluding the capacity of the initial 0.2C activation cycle.
[0064] 6. Impedance test after cycling After 200 cycles at 1C at room temperature, the coin cell half-cell was constant-current charged to 50% of its average discharge capacity after cycling (SOC=50%). After stabilization, electrochemical impedance spectroscopy was performed at 25±2℃. The test frequency range was 100kHz~0.01Hz, and the AC disturbance voltage was 5mV. The charge transfer impedance Rct was obtained by fitting the equivalent circuit.
[0065] The results are shown in Table 1 below.
[0066] Table 1. Electrochemical performance test results of the examples and comparative examples
[0067] As shown in Table 1, the rate performance, cycle retention, and post-cycle impedance of the metal oxide-coated sodium fluorophosphate cathode materials obtained in Examples 1-3 are superior to those in Comparative Examples 1-4. This indicates that the phosphonate anchoring, aluminum salt end-capping initiation, aluminum-zirconium complex precursor pre-adsorption aging, and urea slow-release deposition processes of the present invention can improve the interfacial stability of the materials. Among them, Example 3 has the best overall performance with a 0.2C initial discharge specific capacity of 118.5 mAh / g, a 5C discharge specific capacity of 94.7 mAh / g, a capacity retention of 95.6% after 200 cycles at 25°C, a capacity retention of 92.8% after 100 cycles at 45°C, and a post-cycle Rct of only 71 Ω. Example 1 has a lower coating amount, resulting in relatively insufficient interfacial protection; Example 2 has a higher coating amount, improving cycle stability, but its 5C capacity is lower than that of Example 3, indicating that an excessively thick coating layer increases the resistance to sodium ion transport. Comparative Example 2 did not include tetrasodium 1-hydroxyethylidene-1,1-diphosphonate, Comparative Example 3 did not undergo aluminum salt end capping, and Comparative Example 4 added aluminum zirconium precursor solution and urea simultaneously, resulting in a decrease in rate performance and cycle retention rate and an increase in Rct. This indicates that the surface anchoring, end capping initiation, and sequential control of "pre-adsorption followed by slow-release deposition" of the present invention have a synergistic effect.
[0068] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0069] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A method for preparing a cathode material of sodium fluorophosphate coated with a metal oxide, characterized in that, The metal oxide is a composite oxide containing Al2O3 and ZrO2, and the preparation method includes the following steps performed sequentially: S1. The sodium fluorophosphate matrix was dispersed in an ethanol-water system containing citrate, sodium dihydrogen phosphate, sodium fluoride and sodium 1-hydroxyethylidene-1,1-diphosphonate for phosphonate anchoring pretreatment. After solid-liquid separation and washing with an ethanol-water mixture, the phosphonate-anchored sodium fluorophosphate was obtained. S2. The sodium fluorophosphate pretreated with phosphonate anchoring obtained in step S1 is redispersed in an ethanol-water system, and aluminum salt is added for end-capping initiation treatment to obtain sodium fluorophosphate pretreated with aluminum end-capping. S3. Add an aluminum-zirconium complex precursor solution prepared by an aluminum source, a zirconium source and a complexing agent to the aluminum-end pretreated sodium fluorophosphate dispersion system obtained in step S2, and perform pre-adsorption aging treatment before adding urea in step S4. S4. After the pre-adsorption aging treatment described in step S3 is completed, urea is added and slow-release deposition is carried out under heating conditions to obtain sodium fluorophosphate coated with an aluminum-zirconium composite precursor layer. S5. After solid-liquid separation, washing and drying, the sodium fluorophosphate coated with the aluminum-zirconium composite precursor layer obtained in step S4 is mixed with a sodium- and fluorine-supplementing component including sodium fluoride and sodium dihydrogen phosphate, and subjected to low-temperature heat treatment under an inert atmosphere to obtain the positive electrode material of sodium fluorophosphate coated with metal oxide.
2. The preparation method according to claim 1, characterized in that, In step S1, the sodium ferric fluorophosphate matrix is selected from at least one of Na2FePO4F matrix particles and carbon-coated Na2FePO4F matrix particles; the volume ratio of ethanol to water in the ethanol-water system is 30:70 to 70:30; the citrate is sodium citrate; and the sodium 1-hydroxyethylidene-1,1-diphosphonate is selected from at least one of disodium 1-hydroxyethylidene-1,1-diphosphonate and tetrasodium 1-hydroxyethylidene-1,1-diphosphonate.
3. The preparation method according to claim 1, characterized in that, In step S1, the concentration of sodium dihydrogen phosphate is 0.005–0.05 mol / L, the amount of sodium fluoride is 0.02–0.20% of the mass of sodium ferric fluorophosphate matrix, the amount of sodium 1-hydroxyethylidene-1,1-diphosphonate is 0.02–0.12% of the mass of sodium ferric fluorophosphate matrix, and the pH of the phosphonate anchoring pretreatment is 5.5–6.
8.
4. The preparation method according to claim 1, characterized in that, In step S1, the washing is a single immersion using an ethanol-water mixture, and the washing time is 2 to 10 minutes.
5. The preparation method according to claim 1, characterized in that, In step S2, the aluminum salt is selected from at least one of aluminum nitrate and its hydrate, aluminum chloride and its hydrate, and aluminum isopropoxide, and the amount of the aluminum salt is 0.02 to 0.20% of the mass of the sodium fluorophosphate matrix, calculated as Al2O3.
6. The preparation method according to claim 1, characterized in that, In step S3, the aluminum source is selected from at least one of aluminum nitrate nonahydrate, aluminum chloride hexahydrate, and aluminum isopropoxide; the zirconium source is selected from at least one of zirconium oxychloride octahydrate, zirconium nitrate, and zirconium acetate; and the complexing agent is selected from at least one of citric acid, lactic acid, and malic acid.
7. The preparation method according to claim 1, characterized in that, In step S3, the aluminum source and zirconium source are added at a molar ratio of Al:Zr of 1:(0.1-0.8). The ratio of the total molar amount of aluminum and zirconium in the complexing agent to the total molar amount of aluminum and zirconium in the aluminum-zirconium complexing precursor solution in step S3 is 0.5-2.0:
1. The total amount of aluminum salt in step S2, aluminum source in step S3, and zirconium source in step S3, after being converted to Al2O3 and ZrO2 respectively based on the amount of feed, is 0.3-2.0% of the mass of sodium ferric fluorophosphate matrix.
8. The preparation method according to claim 1, characterized in that, In step S4, the total molar ratio of aluminum and zirconium in the urea to that in the aluminum-zirconium complex precursor solution in step S3 is 5-30:1, the temperature of the slow-release deposition is 75-90°C, and the pH at the endpoint of the slow-release deposition is 6.5-8.
0.
9. The preparation method according to claim 1, characterized in that, In step S5, the washing is performed using at least one of deionized water and an ethanol-water mixture; the sodium and fluoride supplementation components include sodium fluoride and sodium dihydrogen phosphate, wherein the amount of sodium fluoride is 0.02-0.30% of the mass of the sodium ferric fluorophosphate matrix, and the amount of sodium dihydrogen phosphate is 0.02-0.20% of the mass of the sodium ferric fluorophosphate matrix; the low-temperature heat treatment is performed at a temperature of 300-380°C for 1-4 hours, and the inert atmosphere is nitrogen or argon.
10. A cathode material with metal oxide coating of sodium fluorophosphate, characterized in that, The cathode material is prepared by the preparation method according to any one of claims 1 to 9, wherein the cathode material comprises sodium iron fluorophosphate matrix particles and a composite oxide coating layer formed on at least a portion of the surface of the sodium iron fluorophosphate matrix particles, and the composite oxide coating layer comprises Al2O3 and ZrO2.